A Versatile Multiple-Pass Raman System for Industrial Trace Gas Detection - Chunlei Shen (MDPI AG, 2021)
The fast and in-line multigas detection is critical for a variety of industrial applications. In the present work, we demonstrate the utility of multiple-pass-enhanced Raman spectroscopy as a unique tool for sensitive industrial multigas detection. Instead of using spherical mirrors, D-shaped mirrors are chosen as cavity mirrors in our design, and 26 total passes are achieved in a simple and compact multiple-pass optical system. Due to the large number of passes achieved inside the multiple-pass cavity, experiments with ambient air show that the noise equivalent detection limit (3σ) of 7.6 Pa (N2), 8.4 Pa (O2) and 2.8 Pa (H2O), which correspond to relative abundance by volume at 1 bar total pressure of 76 ppm, 84 ppm and 28 ppm, can be achieved in one second with a 1.5 W red laser. Moreover, this multiple-pass Raman system can be easily upgraded to a multiple-channel detection system, and a two-channel detection system is demonstrated and characterized. High utilization ratio of laser energy (defined as the ratio of laser energy at sampling point to the laser output energy) is realized in this design, and high sensitivity is achieved in every sampling position. Compared with single-point sampling system, the back-to-back experiments show that LODs of 8.0 Pa, 8.9 Pa and 3.0 Pa can be achieved for N2, O2 and H2O in one second. Methods to further improve the system performance are also briefly discussed, and the analysis shows that similar or even better sensitivity can be achieved in both sampling positions for practical industrial applications.